L'effet de la thérapie cognitive comportementale sur internet et de la sévérité des symptômes psychologiques sur le soutien émotionnel et tangible post-traitement - Frenette, Émilie (2022)
Exposure to a natural disaster and the presence of post-traumatic stress (PTS) symptoms following a natural disaster leads to a decrease in social support. Few studies have examined ways to improve social support among victims of natural disasters. The first objective of this study was to determine if a 12-session internet-based cognitive behavioral therapy (ICBT) targeting PTS, insomnia and depression symptoms could improve emotional and tangible social support and if so, to determine at which point in the treatment this improvement became significant. The second objective was to examine the predictive value of post-treatment PTS, insomnia, and depression symptom severity on post-treatment emotional and tangible support. The third objective was exploratory and aimed to examine the associations between the use of the platform and emotional and tangible support. One hundred and seventy-eight wildfire evacuees with significant PTS, depression and/or insomnia symptoms were given access to the ICBT. They completed validated self-report questionnaires at pre-and post-treatment to measure social support and symptom severity. Results show that completion of the treatment led to an improvement in emotional support, t(13) = -3.286, p = .006. The improvement in emotional support was also significant for participants that completed at least seven sessions, one of which addressed social support (i.e., session 6), t(15) = -2.143, p = 0.49. Lower post-treatment PTS, β = -.23, p < .05; R² = 0.38, F(4,129) = 13.348, p < .001, and insomnia, β = -.175, p = .04; R² = 0.37, F(4,129) = 19.786, p < .001, symptoms was also associated with higher post-treatment emotional support. ICBT may contribute to improve emotional support through symptom improvement and probably more so when the importance of social support after a disaster and ways to improve it are addressed directly. L'exposition à une catastrophe naturelle ainsi que la présence de symptômes de stress post-traumatique (SPT) entraînent une diminution du soutien ...